Ultrasound of the Brachial Plexus - Griffith, James F. (Seminars in Musculoskeletal Radiology, 2018)
Examination of the brachial plexus with ultrasound is efficient because it allows many parts of the brachial plexus as well as the surrounding soft tissues to be assessed with high spatial resolution. The key to performing good ultrasound of the brachial plexus is being familiar with the anatomy and the common variants. That makes it possible to concentrate solely on the ultrasound appearances free of simultaneously wondering about the anatomy. Ultrasound of the brachial plexus is particularly good for assessing nerve sheath tumor, perineural fibrosis, metastases, some inflammatory neuropathies, neuralgic amyotrophy, and posttraumatic sequalae. It is limited in the assessment of thoracic outlet syndrome and in the acute/subacute trauma setting. This review addresses the anatomy, ultrasound technique, as well as pathology of the brachial plexus from the cervical foramina to the axilla.
Keywords: ultrasound; brachial plexus; axilla; anatomy; diagnosis